Digital Culinary Consumer Cross-Verification: A Comparison of Food Vloggers and E-WOM Credibility - Rizkita, Marsya Aulia; Sudarmiatin, Sudarmiatin (PT Aksara Indo Rajawali, 2025)
This study explores how consumers develop trust in two digital sources—food vloggers and electronic word-of-mouth (e-WoM)—when choosing restaurants. Using a descriptive qualitative method, in-depth interviews were conducted with 18–35-year-old Malang residents who frequently dine out and use social media. Findings reveal that food vloggers effectively raise initial awareness through emotional storytelling and visuals; however, perceived endorsements limit their credibility. In contrast, e-WoM is seen as more trustworthy due to its basis in authentic, user-generated experiences. Trust is shaped by prior experience, the completeness of information, source independence, and review consistency. Consumers apply both emotional and rational evaluations and often cross-check information before making decisions. These insights support classical consumer behavior theories and offer practical guidance for culinary marketers to effectively integrate authentic user reviews with influencer strategies, thereby building sustainable digital trust.